Changing Family Structures in the 21st Century: Trends and Impacts - Venkareddy, Chitkala (AG Volumes, 2025)
Every society has a family, which is a social organisation that brings individuals together in cooperative groupings to manage childbearing and upbringing. Kinship is another name for family relationships, which are social bonds formed by marriage, adoption, or blood. The fundamental unit of society is the family. This article examines the numerous works of literature on how family arrangements are evolving in the twenty-first century. This review highlights significant shifts in family structures in the 21st century, with a growing transition from joint to nuclear families and a steady rise in non-traditional forms such as single-parent, cohabiting, and LGBT families. Despite structural changes, all families seek care, support, and emotional connection. These changes influence individual behavior, parenting roles, and child development. The rise in divorce, delayed marriages, and reduced fertility reflect evolving social values. Increased independence in nuclear families may challenge long-term family stability, with potential shifts toward live-in relationships. Understanding these trends is crucial for shaping responsive policies and sustaining healthy family environments.